The Role of Radio Programs in Agricultural Development Schemes in Osun State, Nigeria - Silas Oghenemaro Emovwodo (Jurnal Spektrum Komunikasi, 2019)
This research attempts to study the role of radio programming on agricultural development schemes in Osun State, Nigeria, with Osun State Broiler Outgrower Production Scheme (OBOPS) And Rural Enterprise and Agricultural Programme (O-REAP) as case study as well as radio’s involvement in agriculture, with a review of an indigenous agricultural program, Aroko Bodunde, broadcast on the Osun State Broadcasting Corporation, Orisun FM, 89.5, Ile-Ife, a community radio station. Powerful-Effect Model and Agenda Setting Theory served as the framework for this study while adopting the descriptive survey of research. Findings revealed that radio programming role in the development of agriculture cannot be overemphasized, as the messages conveyed via the radio wave has helped to increase awareness, inform, enlighten, educate as well as encourage and mobilize listeners to embrace agriculture. Furthermore, findings showed that Orisun FM, 89.5, had a positive influence on listeners which enhanced the development of OBOPS and O-REAP agricultural schemes. It was therefore recommended that governments at all levels in Nigeria should employ community radios in quickening the pace of agricultural development and schemes as radio has proven to be adequately appropriate in giving impetus for the development of all kinds at any level.